Numerical Investigation Of Non- Newtonian Fluid During Mold Filling Process With Phase Change Consideration - Milus, Mohd. Nur Fahmie Ikhwan (Universiti Sains Malaysia, 2018)
A numerical study of Low Density Polyethylene (LDPE) melt on its phase changesbehaviour in mold cavity was carried out. The aim of the study was to observe andunderstand the behaviour of the flow of shear thinning fluids through mold cavity. Threedimensional model simulation of polymer rheology in a dumbbell shape of mold cavitywas used. The ANSYS FLUENT 15.0 simulation software was used to demonstrateviscosity model (Cross Model). The effect of variation in process parameters such as mold temperature and cooling time on the rheological behaviour were studied. The mold temperature was found to have slightly influence on LDPE melt viscosity and flowin the mold cavity and also the phase changes or also known as “frozen skin” layer behaviour. The cooling time also gives the slightly effect on the crystallinity of LDPE in which cooling time plays a role as to determine the degree of crystallinity by giving a time for relaxation-orientation of molecular chains and align at tensile direction. This research was studied by several researchers but most of them did not do the experimental analysis as to compare with simulation results. The comparison between the simulation and experimental analysis must be made in order to determine the discrepancies between theoretical values and actual values and to strengthen the findings. A lot of parameters were considered in this study in order to determine the effect on phase changes and its contribution towards degree of crystallinity. The phase change behaviour was determined by comparing the maximum temperature of ejected specimen from mold in experimental and maximum temperature of specimen model after cooling time finished. Both simulation and experimental results are good and the theoretical and actual values does not show the significant different.